2001
DOI: 10.4049/jimmunol.166.5.2961
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Human Blood Dendritic Cell Subsets by IFNs

Abstract: Based on the relative expression of CD11c and CD1a, we previously identified subsets of dendritic cells (DCs) or DC precursors in human peripheral blood. A CD1a+/CD11c+ population (CD11c+ DCs), also called myeloid DCs, is an immediate precursor of Langerhans cells, whereas a CD1a−/CD11c− population (CD11c− DCs), sometimes called lymphoid DCs but better known as plasmacytoid DCs, is composed of type I IFN (IFN-αβ)-producing cells. Here, we investigate the effects of IFN-αβ and IFN-γ as well as other cytokines o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
216
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(228 citation statements)
references
References 40 publications
(32 reference statements)
11
216
0
1
Order By: Relevance
“…32,44 Studies with LPS and whole bacteria have shown that they too can induce production of this key initiator of immune responses. [33][34][35][36][37] Previously published work using live Mycobacterium tuberculosis and human DCs 37,54 suggest that in this experimental model, large amounts of IFN-a are produced, but in our assay using fixed bacteria this was not seen, suggesting that surface ligation of extracellular receptors may have effects that are different from those seen during intracellular replication. Figure 8.…”
Section: Discussionmentioning
confidence: 69%
“…32,44 Studies with LPS and whole bacteria have shown that they too can induce production of this key initiator of immune responses. [33][34][35][36][37] Previously published work using live Mycobacterium tuberculosis and human DCs 37,54 suggest that in this experimental model, large amounts of IFN-a are produced, but in our assay using fixed bacteria this was not seen, suggesting that surface ligation of extracellular receptors may have effects that are different from those seen during intracellular replication. Figure 8.…”
Section: Discussionmentioning
confidence: 69%
“…The importance of the CD80/CD86-CD28 system in T cell responses has been well demonstrated [10,20,21,29] . The CD80 and CD86, members of the immunoglobulin super gene family, are encoded by separate genes and provide costimulatory function for APC-dependent T-cell activation both in vivo and in vitro [25][26][27][28] . A previous study reported that most tumor tissues, like those from the nonhematopoietic origin, did not express costimulatory molecules, which would render T cells unresponsive for the specific antigens [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Most myeloid DCs have some capacity to produce IL-12 and, thereby, to induce Th1 development. However, this capacity varies with the conditions of their maturational stage or stimulation delivered to DCs [43][44][45][46][47][48]. A similar functional plasticity is observed in IPC-derived DCs [8, 49 -51].…”
Section: Ipc-derived Dcs In Adaptive Immunity Possible Involvement Imentioning
confidence: 95%